2021
DOI: 10.1088/1742-6596/1785/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of turbulent transport coefficients in 2D interchange dominated ExB turbulence involving flow shear

Abstract: While turbulent transport is known to dominate the radial particle and energy transport in the plasma edge, a self-consistent description of turbulent transport in mean-field transport codes remains lacking. Mean-field closure models based on the turbulent kinetic energy (k ⊥) and turbulent enstrophy (ζ⊥) have recently been proposed to self-consistently model this transport. This contribution analyses the diffusive particle transport relations of these models by means of the Bayesian framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 23 publications
4
25
0
Order By: Relevance
“…The last term on the right-hand side of Equation ( 41), −p ′ V ′ E ⋅ ∇ ln B 2 , is the source of 𝜅 due to the interchange mechanism. This was found to be the dominant source of 𝜅 in recent studies of interchange E × B drift turbulence for the SOL using TOKAM2D simulations, [17,20,24,25] which form the basis for the present work. Interestingly, no additional closure is needed † The full form of the polarization current and additional currents could easily be included, but we will neglect them in a later stage, so we chose to leave them out from the start for clarity of the derivation.…”
Section: Interchange Source Of 𝜿mentioning
confidence: 72%
See 4 more Smart Citations
“…The last term on the right-hand side of Equation ( 41), −p ′ V ′ E ⋅ ∇ ln B 2 , is the source of 𝜅 due to the interchange mechanism. This was found to be the dominant source of 𝜅 in recent studies of interchange E × B drift turbulence for the SOL using TOKAM2D simulations, [17,20,24,25] which form the basis for the present work. Interestingly, no additional closure is needed † The full form of the polarization current and additional currents could easily be included, but we will neglect them in a later stage, so we chose to leave them out from the start for clarity of the derivation.…”
Section: Interchange Source Of 𝜿mentioning
confidence: 72%
“…The model further assumes that 𝜌 L is the relevant length scale, implying eventually the time scale T ∼ 𝜌 L ∕ √ 𝜅∕m. The possibility for a diffusive closure is further confirmed in the context of isothermal drift-wave turbulence and anisothermal 2D electrostatic interchange simulations in Reference [24], but the proportionality constant may differ depending on the regime. Furthermore, in Reference [25] it is additionally shown that the electron and ion heat fluxes due to E × B fluctuations can be approximated with a diffusive relation, where the diffusivities follow the same characteristic scaling as D E×B up to a constant of order unity:…”
Section: Closure Of the Transport Fluxesmentioning
confidence: 79%
See 3 more Smart Citations